GE_GERICHTE C/20944/2012 vom 8. Dezember 2016 - GE Cour de justice (2016)
CONDUITE DU PROCÈS; DÉCISION ; DIVORCE ; DROIT DE GARDE ; OBLIGATION D'ENTRETIEN ; ENFANT | CPC.381.a; CPC.316.3; nCC.276.1.2; nCC.276.a.2; nCC.285; nCC.286.a.1;